Are young adults' discussions of public health nutrition policies associated with common food industry discourses? A qualitative pilot study. (22nd February 2021) - Howse, Eloise; Hankey, Catherine; Bauman, Adrian; Freeman, Becky
Abstract: Objective : Unhealthy diets are a key risk factor for chronic disease, with young adults (18–30 years old) in high‐income countries like Australia and the UK particularly at risk. Improved public health nutrition policies can help address unhealthy diets in the population, but many of the more regulatory policies are opposed by food industry groups. This research explores how young adults in Australia and the UK discuss a range of topical public health nutrition policies and analyses whether and how their views may be associated with food industry discourses. Methods : Eight focus groups were held in Sydney, Australia, and Glasgow, UK, with a total of thirty young adults participating. A deliberative‐style method was used in the focus groups to generate discussion about six public health nutrition policies, such as taxation of sugar‐sweetened beverages and restrictions on advertising of less‐healthy foods. Discourse analysis was used to examine participants' discussions. Results : Twenty discourse codes were developed iteratively from the focus group data. These were thematically linked with nine food industry discourses found in the peer‐reviewed literature, including industry self‐regulation, personal responsibility, corporate social responsibility and challenging nutrition science. Conclusions : These results demonstrate there is an association between common food industry discourses and some young adults' views about public health nutrition policies. Implications for public health : Identifying, engaging with and responding to common industry discourses is a priority in order to build greater public support and acceptability of policies that will improve diet and prevent chronic disease.